The G Protein-Coupled Receptor (GPR) 15 Counteracts Antibody-Mediated Skin Inflammation - Jegodzinski, Lina; Sezin, Tanya; Loser, Karin; Mousavi, Sadegh; Zillikens, Detlef; Sadik, Christian D. (Frontiers in Immunology, 2020)
The G protein-coupled receptor 15 (GPR15) has recently been highlighted as an important regulator of T cell trafficking into the gut under physiological and pathophysiological conditions. Additionally, circumstantial evidence has accumulated that GPR15 may also play a role in the regulation of chronic inflammation. However, the (patho)physiological significance of GPR15 has, in general, remained rather enigmatic. In the present study, we have addressed the role of GPR15 in the effector phase of autoantibody-mediated skin inflammation, specifically in the antibody transfer mouse model of bullous pemphigoid-like epidermolysis bullosa acquisita (BP-like EBA). Subjecting Gpr15-/- mice to this model, we have uncovered that GPR15 counteracts skin inflammation. Thus, disease was markedly aggravated in Gpr15-/- mice, which was associated with an increased accumulation of γδ T cells in the dermis. Furthermore, GPR15L, the recently discovered cognate ligand of GPR15, was markedly upregulated in inflamed skin. Collectively, our results highlight GPR15 as counter-regulator of neutrophilic, antibody-mediated cutaneous inflammation. Enhancing the activity of GPR15 may therefore constitute a novel therapeutic principle in the treatment of pemphigoid diseases, such as BP-like EBA.